1991
DOI: 10.3758/bf03203387
|View full text |Cite
|
Sign up to set email alerts
|

CAI-enhanced exam performance in a research design course

Abstract: . InThe efficacy of computer-assisted instruction (CAl) for increasing test performance in an experimental design course was tested using two commercially available programs to supplement course material. CAl was used to supplement course content for one of three examinations. Comparisons were also made with performance on the exams from 2 previous years. The results indicate a significant enhancement of performance by CAL A number of logical, insightful articles have been written on how computers could, theor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In a class on abnormal psychology, Lambert and Lenthall (1989) used a pre-, posttest design to assess the effects of case simulations on computer anxiety. Duncan (1991) attempted to resolve some of these difficulties through the use of CAl in the second of four components of her research design course. Some investigators (Tobias, 1987) have indicated that acquisition of concepts in different sections of the same course may require the utilization of different cognitive strategies or be most compatible with particular cognitive styles.…”
Section: Research Design Considerations: Internal Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…In a class on abnormal psychology, Lambert and Lenthall (1989) used a pre-, posttest design to assess the effects of case simulations on computer anxiety. Duncan (1991) attempted to resolve some of these difficulties through the use of CAl in the second of four components of her research design course. Some investigators (Tobias, 1987) have indicated that acquisition of concepts in different sections of the same course may require the utilization of different cognitive strategies or be most compatible with particular cognitive styles.…”
Section: Research Design Considerations: Internal Validitymentioning
confidence: 99%
“…It is important to understand the effect of CAl on students' attitudes toward computer-based learning and toward the particular software packages employed. A number of studies (Cordell, 1991;Duncan, 1991;Goolkasian, 1989;Lambert & Lenthall, 1989) have included this outcome measure, and several scales (Heinssen, Glass, & Knight, 1987;Meier, 1988;Simonson, Maurer, Montag-Torardi, & Whitaker, 1987) have been developed to facilitate this process. Most have reported positive attitudes, although Cordell did not include a complete summary of her feedback questionnaire.…”
Section: Outcome Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…PSY 5 Psychology ; WWW 5 World Wide Web. who selected electronic options also performed slightly better on the nal exam, although this is not inconsistent with research (Duncan, 1991;Goolkasian, 1989;Marcoulides, 1990;Worthington, Welsh, Archer, Mindes, & Forsyth, 1996), which suggests computer-based instruction improves test performance. Conversely, students who elected electronic options tended to perform slightly worse on papers and presentations, perhaps indicating that they were initially weaker students whose performance was enhanced by means of computerized instruction.…”
Section: Figure 4 Percent Of Psy101 Students Selecting Other Optionsmentioning
confidence: 51%
“…Duncan (1993) also articulated the controversy over the proper choice of dependent variable. Some argue for domain-specific measures, such as objective indices that focus on the concepts examined in CAl experiences (Duncan, 1991;Petty & Rosen, 1990;Welsh & Null, 1991). Others argue for more generalized measures of learning (Hannafin & Carney, 1991).…”
mentioning
confidence: 99%